2011
DOI: 10.1007/s12471-011-0141-1
|View full text |Cite
|
Sign up to set email alerts
|

Ebstein’s anomaly may be caused by mutations in the sarcomere protein gene MYH7

Abstract: Ebstein’s anomaly is a rare congenital heart malformation characterised by adherence of the septal and posterior leaflets of the tricuspid valve to the underlying myocardium. Associated abnormalities of left ventricular morphology and function including left ventricular noncompaction (LVNC) have been observed. An association between Ebstein’s anomaly with LVNC and mutations in the sarcomeric protein gene MYH7, encoding β-myosin heavy chain, has been shown by recent studies. This might represent a specific subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Patients with Ebstein anomaly also suffer from a myocardial disease known as left ventricular noncompaction (LVNC). 15 This condition is brought about by abnormalities in structural proteins which are important for heart contraction. This malformation has been linked to the gene MYH7, where mutations result in spongelike muscle tissue protruding into the left ventricle, impairing contraction.…”
Section: Geneticsmentioning
confidence: 99%
“…Patients with Ebstein anomaly also suffer from a myocardial disease known as left ventricular noncompaction (LVNC). 15 This condition is brought about by abnormalities in structural proteins which are important for heart contraction. This malformation has been linked to the gene MYH7, where mutations result in spongelike muscle tissue protruding into the left ventricle, impairing contraction.…”
Section: Geneticsmentioning
confidence: 99%
“…Recent studies have identified MYH7 mutations as a cause of Ebstein's anomaly associated with LVNC and other congenital heart disease (CHD). [1] So far, there were only three reported cases of biventricular non-compaction associated with Ebstein's malformation. [38] All these cases had LV dilatation and reduced systolic function in varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is characterized by apical displacement and adherence of the septal and posterior leaflets of the tricuspid valve to the underlying myocardium, thereby displacing the functional tricuspid orifice apically and dividing the right ventricle into two portions. [1] The main hemodynamic abnormality which leads to symptoms is tricuspid valve incompetence. These patients may be asymptomatic or experience right-sided heart failure, cyanosis, arrhythmias and sudden cardiac death (SCD).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations